Influencia de los estilos de crianza en la violencia Filio-Parental en niños y adolescentes. - Murillo Rosero, Danilo Sebastian (2024)
This study seeks to identify the relationship between parenting styles and child-to-parent violence, through a well-founded characterization and definition of each variable and the specification of the types of child-to-parent violence. For this, a bibliographical research was carried out, of a cross-sectional design with a correlational scope and with a mixed approach, in a sample of 26 scientific articles which were chosen based on the selection criteria, a registration table and the matrix to qualify. methodological quality (CRF-QS). The results of the review revealed that 65% of the authors identified the authoritarian, negligent and permissive parenting styles with the greatest relationship with respect to child-to-parent violence (CPV). These parenting styles do not allow an adequate development of emotional intelligence, nor do they promote values such as respect and empathy, which can lead children to resort to aggressiveness as the main way of resolving conflicts. For their part, the remaining 35% of authors pointed out that VFP is a multicausal phenomenon, influenced by factors such as gender, the social and school environment, substance use, personality characteristics and mental health of both children and adolescents. like parents. Among the main types of VFP are physical violence, psycho-emotional, economic and patrimonial violence. In conclusion, this study highlights the importance of parents acquiring not only proper parenting skills but also social skills, emotional intelligence, and self-esteem to prevent child-to-parent violence.